The Correlation between the Level of Doxorubicin-Induced Cardiac Damage and Serum Soluble Fas in an Experimental Rat Model - Kose, Dogan; Ozdemir, Hulya; Celik, Zeliha Esin; Unlu, Ali; Artac, Hasibe; Koksal, Yavuz (Indian Journal of Medical and Paediatric Oncology, 2018)
Aim: This study was planned to research the relationship between doxorubicin cardiomyopathy and the soluble Fas (sFas) level. Materials and Methods: Two groups of rats were included in the study. The control group was given physiological saline, while the study group was given doxorubicin. The rats, whose blood samples were taken weekly, were sacrificed and their myocardial tissues were removed. The tissues were examined in terms of morphological changes and surface Fas expression, while the blood samples were examined in terms of sFas level. Results: In the study group, the sFas levels at 2nd–9th weeks were higher than those found at 1st week before administrating the drug, and the increase at 2nd–7th weeks was meaningful. In addition, sFas levels were gradually increased each week during 1st–5th weeks when compared to the values of a previous week, and the increase during the first 4 weeks was meaningful. After the 5th week, the values gradually decreased each week. The mean values of the study group at 1st–8th weeks were higher than those of the control group, and the increases at 2nd–8th weeks were meaningful. The severe forms of interfibrillar hemorrhage, vascular dilatation, myocardial necrosis, inflammatory infiltration, and splitting of muscle fibers occurred with 15, 15, 17.5, 20, and 22.5 mg/kg dose of medicine, respectively. Conclusions: As the tissue injury increased, the increasing cell-surface Fas expression and sFas plasma level at the acute phase of doxorubicin-related cardiotoxicity decreased. The sFas level determined at acute phase may be helpful in predicting the existing injuries and possible late-term problems.
Keywords: Cardiac; doxorubicin; fas; rat